Analisis Kinerja Pondok Pesantren Darul Qolam Binjai dalam Menciptakan Mutu Lulusan - Sofian, Sofian; Prasetia, Indra; Amini, Amini (UMSU, 2025)
The study aims to determine the Performance Analysis of Darul Qolam Islamic Boarding School. The method used is a case study research type with interview data collection techniques, observation and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions. This research was carried out at Darul Qolam Islamic Boarding School with the subject of the researcher and the object of the research being the principal, vice principal, administration, and teachers. The results of the study on the performance of the Islamic boarding school include the following activities: Managing and Developing Vision, Mission and Objectives, Analyzing the weaknesses and strengths of external factors, Caregivers who act as Parents and determining strategies. Likewise, the performance of the Darul Qolam Islamic Boarding School to create quality graduates, namely, the maximum involvement of teachers, with the leadership of the head of the madrasah who must have and understand a clear work vision, be able and willing to work hard, have a high work motivation, be diligent and steadfast in working, provide optimal service, and strong work discipline. In addition, it must also improve the competence and profession of teachers. Improving the quality of graduates who have intelligence is the hope of the madrasah, parents, the wider community, and the government. Realizing it by Managing the Quality of Tahfidz al-Quran, Minimum Limits for Student Promotion and Graduation Standards, improving quality culture, Improving the Quality of Teacher Competence.